(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
The COVID-19 pandemic in Indonesia has been going on since the beginning of 2020. During the pandemic, various efforts to prevent transmission were carried out, limiting public visits to health care facilities. Health services must continue to run; therefore, multiple efforts must be made to support this, one of which is telenutrition. The study aimed to determine the effect of telenutrition on the number of visits to the nutrition polyclinic at the Kramat Jati Public Health Center. This study used a quasi-experimental design with a pre-post design approach without a control group design, which aims to determine the differences before and after treatment. Results showed that in the Telenutrition program, polyclinic nutrition visits increased dramatically to 8-13 times from before. The results of the Paired Sample t-test obtained a significant value with ρ-value = 0.000, there is an influence of telenutrition on polyclinic nutrition visits at the Kramat Jati Public Health Center. The results of feedback from patients, the response of officers in dealing with patients was 98.4 percent excellent, 96 percent service was on time, and 98.4 percent of the service methods provided by officers were perfect. The study concluded the telenutrition program could improve performance and become a solution for nutrition services during the COVID-19 pandemic.